Capital structure with dividend restrictions - Wald, John (Journal of Corporate Finance, 1999)
This paper develops a symmetric information model of a new firm which incorporates a constraint on dividend payments known as a balance sheet test. This test solves moral hazard problems that arise in credit markets where complete contracting over future actions is not possible. This constraint breaks down the traditional symmetric information result of separability between financial and real variables, and thus maximizing shareholder returns in this setting is not equivalent to maximizing total firm value. As a consequence, more profitable firms, those with a higher average product of capital, will have lower debt/equity ratios. Debt/equity ratios will be positively correlated with the firm's physical capital and negatively correlated with the firm's market power.